Challenges in the pursuit of justice for East Timor’s Great Famine (1977–1979) - Hearman, Vannessa (Taylor & Francis, 2022)
Despite its devastating impact on the population, the 1977–1979 famine in East Timor scarcely features in global studies of hunger. This article traces how the famine was dealt with in international politics during the Indonesian occupation (1975–1999), and in Timor-Leste during the United Nations administration and as an independent nation-state. The East Timor case extends our knowledge of the workings of conflict-induced famines, provides insights into the attempts by transnational activists and diasporic actors to mobilise international action on crises such as famine, and examines the options for dealing with famine and its community-wide legacies in post-conflict societies including under a transitional justice model. By analysing the activities of the country’s transitional justice institution, the Commission for Reception, Truth and Reconciliation (Comissão de Acolhimento, Verdade e Reconciliação, CAVR) and its successor, the Centro Nacional Chega! (CNC), as well as grassroots initiatives, the article outlines some of the challenges of delivering justice for famine victims and survivors in post-conflict societies.